The current state of sustainability reporting and perceptions of Corporate Sustainability Reporting Directive (CSRD) in listed international companies - Jyrinki, Milja (My University, 2024)
Sustainability has become an increasingly important topic to focus on. The importance of sustainability has also become crucial for companies to consider in their operations, and many companies have also started to voluntarily report about their sustainability. During the last decade, the European Union has also started to regulate sustainability reporting, and in 2023, it strengthened the regulation when Corporate Sustainability reporting Directive (CSRD) entered into force. CSRD will affect approximately 50 000 companies. The directive comes into effect gradually. First, in financial year 2024 it will only concern companies which have already been obliged for sustainability reporting due to Non-Financial Reporting Directive (NFRD) which entered into force 2014 to regulate large, public interest companies’ sustainability reporting. In financial year 2025, also other large companies become subject to CSRD, and, in financial year 2026 CSRD will con- cern also listed SMEs. Due to the new directive, obligation for sustainability reporting broadens to concern also many companies that has not been required to publish sustainability reports previously, and the reporting will be more regulated. As a part of the new directive, the European Union introduced the new European Sustainability Reporting Standards (ESRS) which all companies that are subject to CSRD must adopt in their sustainability reporting. The new directive and common standards aim to harmonise the reporting and increase the transparency, comparability and reliability of the reports. This study focuses on the sustainability reporting of listed international companies that have not been required to report about their sustainability. The aim of the research is to study the current state of sustainability reporting and the companies’ perceptions of CSRD. The study is qualitative by nature, and semi-structured interviews are used for the data collection. The results of this study are aligned with the previous studies and show that many companies have started voluntary sustainability reporting. However, there are no established practices for reporting. Similarly as previous studies, also this study highlights the stakeholders’ perspective and involvement in reporting practices. Stakeholders’ demands seem to be one of the key drivers for the companies to start to report about their sustainability. Moreover, the study provides in- sights of companies’ perceptions to CSRD and preparation for it.

Vastuullisuuden merkitys yhä korostuneempi, ja sen huomioiminen on noussut myös merkittävään rooliin yritysten toiminnassa. Monet yritykset ovat myös aloittaneet raportoimaan vastuullisuudestaan. Viimeisen vuosikymmenen aikana myös Euroopan Unioni on alkanut säätelemään vastuullisuusraportointia, ja vuonna 2023 sääntelyä vahvistettiin, kun uusi kestävyysraportointidirektiivi (Corporate Sustainability Reporting Directive, CSRD) astui voimaan. Direktiivin piirissä tulee olemaan noin 50 000 yritystä. Uusi direktiivi tulee voimaan asteittain. Ensin, tilikautena 2024 suuret, yleisen edun kannalta merkittävät yritykset, jotka ovat jo aiemmin olleen velvoitettuja vastuullisuusraportointiin tulevat kestävyysraportointidirektiivin piiriin. Sen jälkeen, tilikaudella 2025 muut suuret yritykset tulevat direktiivin piiriin, ja 2026 direktiivi laajenee entisestään koskemaan myös listattuja pieniä ja keskisuuria yrityksiä. Uuden direktiivin myötä vastuullisuusraportointi tulee pakolliseksi isommalle osalle yrityksistä, ja siten ajankohtaiseksi myös monille yrityksille, jotka eivät ole aiemmin olleet velvoitettuja vastuullisuusraportointiin. Direktiivi myös säätelee raportointia enemmän. Osana uutta direktiiviä Euroopan Unioni esitteli myös uudet kestävyysraportointistandardit (European Sustainability Reporting Standards, ESRS), jotka kestävyysraportoinnin piirissä olevien yritysten tulee ottaa käyttöön raportointiinsa. Uusi direktiivi ja yhteiset standardit pyrkivät harmonisoimaan yritysten vastuullisuusraportointia, ja tekemään siitä luotettavampaa ja vertailukelpoisempaa. Tämä tutkimus keskittyy sellaisten listattujen ja kansainvälisesti toimivien yritysten vastuullisuusraportointiin, jotka eivät ole olleet velvoitettuja raportoimaan vastuullisuudestaan. Tutkimuksen tavoitteena on tutkia yritysten nykyisiä vastuullisuusraportointikäytänteitä, sekä yritysten näkemyksiä uudesta kestävyysraportointidirektiivistä. Tutkimus on luonteeltaan kvalitatiivinen ja tutkimusaineiston keruuseen on hyödynnetty puolistrukturoituja haastatteluja. Tutkimuksen tulokset ovat linjassa aiempien tutkimusten tulosten kanssa. Moni yritys on aloittanut raportoimaan vastuullisuudestaan vapaaehtoisesti. Tulosten perusteella vastuullisuusraportointiin ei kuitenkaan ole vakiintuneita käytänteitä yritysten välillä. Kuten aiemmat tutkimukset, myös tämä tutkimus osoittaa, että sidosryhmien odotukset vastuullisuusraportoinnille on yksi merkittävimmistä syistä aloittaa vastuullisuusraportointi. Lisäksi tutkimus tarjoaa tietoa yritysten näkemyksistä kestävyysraportointidirektiivistä sekä siitä, miten yritykset ovat alkaneet valmistautua siihen.
Keywords: sustainability reporting; sustainable development; international corporations; fi=Kansainvälinen liiketoiminta|en=International Business|; Master's Degree Programme in International Business